2021
DOI: 10.2106/jbjs.rvw.20.00152
|View full text |Cite
|
Sign up to set email alerts
|

Surfing Injuries

Abstract: » Surfing is safe: the risk of injury ranges from 0.26 to 0.90 injuries per surfer per year, 0.06 to 3.5 injuries per 1,000 days of surfing, and 1.1 to 13.0 injuries per 1,000 hours of surfing.» The most common acute surfing injuries are lacerations, contusions, and sprains; the head and the neck as well as the lower extremities are the locations that are affected most.» The most common mechanism of injury is striking a surfer’s own board or that of another surfer.» A pathology that is unique to surfers is sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Studies on ocean surfing have reported that most injuries are in the lower extremities 2 4 , 7 , 9 and head/face. 1 , 6 In ocean surfing, lacerations have been reported as the most common type of injury, 4 , 7 , 9 whereas our findings indicated that a contusion was the most commonly reported injury type in river surfing. This resonates with the different distributions of the injury mechanism mentioned before.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Studies on ocean surfing have reported that most injuries are in the lower extremities 2 4 , 7 , 9 and head/face. 1 , 6 In ocean surfing, lacerations have been reported as the most common type of injury, 4 , 7 , 9 whereas our findings indicated that a contusion was the most commonly reported injury type in river surfing. This resonates with the different distributions of the injury mechanism mentioned before.…”
Section: Discussionmentioning
confidence: 44%
“…The most common mechanism of injury was contact with the surfer’s own board in 55%, contact with the sea floor in 17%, and contact with another surfer’s board in 12%. 9 Comparable results were published by Klick et al 4 in 2016, by Minghelli et al 7 in 2018, and recently by Bickley et al 1 in 2021. These authors also found that the most commonly reported mechanism of injury was contact with the surfer’s own board or another surfer’s board, followed by contact with the sea floor.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…1,[3][4][5] Indeed, it has been estimated that up to one-third of recreational surfers sustain a major traumatic injury every year, and systematic review has reported the overall incidence of traumatic injury to range from 0.06 to 3.5 injuries per 1000 days of surfing, and 0.74 to 6.6 injuries per 1000 hours surfed. 4,6,7 Surfing has been estimated as the cause of 5.9% of all aquatic-related craniofacial injuries presenting to the emergency department (ED), and this number is expected to increase. 8 Although total body injury patterns suffered by surfers have been studied, there is less analysis specifically detailing the characteristics of surfingrelated craniofacial trauma.…”
mentioning
confidence: 99%
“…Surfing is considered a safe sport, one associated with few serious injuries and very rare drownings 1 . Little is known, however, about the risks of storm surfing, the practice of surfing large storm-generated waves.…”
mentioning
confidence: 99%